(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this research was to see how Moringa honey affected nutritional intake and malondialdehyde levels in pregnant women.The study was an experimental study using a randomized controlled trial (RCT) design. The study was conducted in Maros regency, Indonesia, specifically in Turikale and Lau Community Health Center (Puskesmas). A total of 42 2nd trimester pregnant women were recruited, dividing into two groups of intervention; Moringa honey group (n=21) and control group (n=21) who received 15 ml of honey per day. In addition, pregnant women were given blood-boosting vitamins (Fe) to consume in the night. The intervention was given to the mothers for 8 weeks. Urine samples were collected to assess malondialdehyde levels using the ELISA method.The majority of respondents (30.9%) were between the ages of 26 and 30, had more than one child (45.2%), and earned between Rp 1.000.000 - Rp 3.000.000 (47.6%). The finding shows that the intervention group had an average difference in energy 1418 ± 584 kcal, 98 ± 61g of protein, 320 ± 134g of carbohydrates, 321 ± 46mg of iron, 97 ± 53mg of vitamin C, compared to those in the control group (1260 ± 696kkal, 65 ± 18.31g, 193 ± 87g, 105 ± 50mg, 89 ± 46mg, respectively; p value=0.001. In addition, the increase of MDA levels in the intervention group was not significantly higher than in control group (8.32 ± 6.80 vs 6.46 ± 14.80; p=0.606). In conclusion, the moringa honey has a greater nutritional content than regular honey, resulting in a higher nutrient intake, but was not difference in contributing to MDA level.